PENERAPAN KONSEP FINITE STATE AUTOMATA (FSA) PADA MESIN PEMBUAT MINUMAN KOPI OTOMATIS - Wamiliana Wamiliana; Didik Kurniawan; Rizky Indah Melly (Universitas Lampung, 2013)
This research discusses about a simulating application for automatic coffee machine which can do processes of making 7 types of choices of drinks; coffee, milk, chocolate, coffee milk, coffee brown, mocha, and chocolate milk automatically. In this application, the concept of Finite State Automata (FSA) was applied to recognize and to capture the pattern on the process for making coffee drinks. In this application, Finite State Automata (FSA) was applied to read input symbols given from the starting state to the final state in order to get the language recognized by the machine. Further, the process will be done accordance with the read language.Keywords: Coffee Machine, Finite State Automata (FSA), Language and Automata Theory.